Efficient CRISPR/Cas9 Genome Editing in Alfalfa Using a Public Germplasm - Bottero, Emilia; Massa, Gabriela; González, Matías; Stritzler, Margarita; Tajima, Hiromi; Gómez, Cristina; Frare, Romina; Feingold, Sergio; Blumwald, Eduardo; Ayub, Nicolás; Soto, Gabriela (Frontiers in Agronomy, 2021)
Because its ability to acquire large amounts of nitrogen by symbiosis, tetraploid alfalfa is the main source of vegetable proteins in meat and milk production systems in temperate regions. Alfalfa cultivation also adds fixed nitrogen to the soil, improving the production of non-legumes in crop rotation and reducing the use of nitrogen fertilizers derived from fossil fuel. Despite its economic and ecological relevance, alfalfa genetics remains poorly understood, limiting the development of public elite germplasm. In this brief article, we reported the high-efficiency of alfalfa mutagenesis by using the public clone C23 and the CRISPR/Cas9 system. Around half of the GUS overexpressing plants (35S-GUS under C23 genomic background) transformed with an editing plasmid containing two sgRNAs against the GUS gene and the Cas9 nuclease exhibited absence of GUS activity. Nucleotide analysis showed that the inactivation of GUS in CRISPR/Cas9-editing events were produced via different modifications in the GUS gene, including frameshift and nonsense mutations. Using the CRISPR/Cas9 system and two sgRNAs, we have also edited the alfalfa gene NOD26, generating plants with different doses of alleles at this locus, including complete gene knockout at high efficiency (11%). Finally, we discuss the potential applications of genome-editing technologies to polyploid research and to alfalfa improvement public programs.